2014
DOI: 10.1016/s0924-9338(14)77772-7
|View full text |Cite
|
Sign up to set email alerts
|

EPA-0337 – Is opioid dependency related to coping strategies?

Abstract: Introduction:Using opioid for recreational purposes has a very long history in Iran. Social influence is a useful framework in understanding how the social environment affects the individual's behavioral choices to use drugs.Objectives:This study aimed to compare coping styles between opioid dependent and healthy controls.Methods:This study compared opioid dependent individuals entering methadone maintenance treatment program (n=150) with healthy controls (n= 225) on measures of coping strategies with Jalowiec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In a study conducted by Altunay et al (23) on smokers with psoriasis, it was found that they are less likely to seek social support, which is one of the problem-focused strategies. A similar result has also been reported among opioid addicts (24). Of course, in some studies, the positive effect of emotion-focused strategy on increasing stress adaptation has been indicated (25).…”
Section: Discussionsupporting
confidence: 79%
“…In a study conducted by Altunay et al (23) on smokers with psoriasis, it was found that they are less likely to seek social support, which is one of the problem-focused strategies. A similar result has also been reported among opioid addicts (24). Of course, in some studies, the positive effect of emotion-focused strategy on increasing stress adaptation has been indicated (25).…”
Section: Discussionsupporting
confidence: 79%